Ensino de astronomia mediado pelas tecnologias da informa??o e comunica??o (tic): propostas de abordagem e an?lise - Jesus, Milena dos Santos Pedreira de (2015)
We are experiencing a period of transformation of teaching and learning techniques in school as an institution. Beyond its ?walls?, new technologies are developed and gradually incorporated into the daily lives of people. These same educational institutions try to keep up with changes upgrading themselves technologically acquiring equipment such as computers, tablets, televisions and internet connections so that teachers can use these media in the classroom. Despite this, the reflection on the best approaches to use these technologies for education is set aside. Thus, several questions remain open. Can the use of technological resources contribute to significant student learning? What are the new challenges that come to school? How teachers can deal with them? This work aims to discuss such issues and thus contribute to the reflection on the significant learning in the teaching-learning process of Astronomy and other sciences.